Risk Tolerance Estimation Bias: The Age Effect - Grable, John E.; McGill, Samantha; Britt, Sonya L. (My University, 2010)
Older individuals are generally assumed to be less risk tolerant compared to others. The purpose of this research was to test how accurately working adults at different ages in the lifespan estimate their risk-taking propensity. Differential predictions, using ANOVA and regression analyses, were assessed. Findings suggest that younger working adults tend to over-estimate their risk tolerance compared to older working adults. Although those in middle-age were shown to under-estimate their risk tolerance compared to the youngest working adults, the results were not significant. A discussion of findings is presented with the proposition that over- and under-estimation of risk tolerance might help explain the types of risk-taking behaviors engaged in by individuals over time.
Keywords: Risk tolerance; Estimation bias; Differential prediction